New Highlander Music in the Age of Globalization as Illustrated by the “Trebunie-Tutki” Band - Kłych, Małgorzata (Studia Etnologiczne i Antropologiczne, 2014)
Music has accompanied people for thousands of years. It is sometimes necessary partner at work, at play, at rest. With its help the people most fully and most beautifully able to express their feelings. Is folk music still alive or what was left of the old tradition of music-making can still grab us and amaze? Is it possible to develop creative Polish folk? In recent years, there are clear relapse intotraditional music, you can even talk about the Renaissance.